Brazilian representativity crisis:: influence of group hegemony and representative democracy - Alves, Larissa Moreira Ribeiro; Mencher, Yasmim (Revista de Ciências do Estado, 2018)
This article aims to discuss the oligarchic manifestations in Brazil over time and its reflection in the popular exercise of citizenship, as well as in the political representation of the non-dominant classes. The argumentation was built based on well-established authors on the themes of colonelism and clientelism, such as José Murilo de Carvalho and Victor Nunes Leal, and democracy, such as Norberto Bobbio and Jacques Rancière, therefore, the methodology applied was a bibliographical review about the theme. In doing so, we seek to illustrate how participatory democracy in the brazilian context has made progress, with the inclusion of mechanisms of participation, and setbacks, according to the intensity of influence from the dominant groups. Finally, we pursue to reflect on the impact of this panorama on the behavior of citizens in relation to politics.